Experience of an Italian Hospital Claims Management Committee: A tool for extrajudicial litigations resolution. (February 2020) - Gualniera, Patrizia; Mondello, Cristina; Scurria, Serena; Oliva, Antonio; Grassi, Simone; Pizzicannella, Jacopo; Alibrandi, Angela; Sapienza, Daniela; Asmundo, Alessio
Highlights: Italian medical malpractice has great impact on National expenditure. Claims Management Committee (CMC) is the tool for Hospital claims analysis. CMC needs efficient medicolegal activities. CMC has higher probability of litigation amicable settlement than Insurance system. CMC could allow to saving the costs related to medical liability. Abstract: Litigation related to medical liability has a great impact on Italian healthcare expenditure. Recently, many Italian Regions have adopted a "self-insurance system" and, in Sicilian Hospitals, were established the Claims Management Committees (CMC) to provide the direct management of claims. Here the experience of a Sicilian University Hospital CMC was described to analyze the claims features and their outcomes providing evidence on CMC usefulness. The analysis involved claims for compensation received during 4 years, using data obtained by a retrospective analysis of claims database created by Forensic Medicine Service. Claims data, obtained from the insurance broker, were used to perform the statistical comparison. During the examined period a total of 377 claims were received by CMC, respectively 63.6% for professional liability and 36.4% for other causes (damages not related to medical malpractice). The prevalence of complaints about malpractice regarded surgery. The CMC had expressed an opinion on 120 claims related to malpractice with the percentages of admission or rejection of liability respectively of 55% and 45%. The statistical analysis revealed a greater number of lawsuits in the Insurance system and, moreover, the CMC higher probability to reach the amicable settlement of litigations. CMC provides specific data on claims trend and economic expenditure, demonstrating its usefulness for analysis and monitoring the causes of patients/people damage. It is a tool for medical malpractice risk assessment and prevention. It can encourage the amicable settlement and prevention of civil action. It seems to be an efficient system to reduce the health liability costs.